The effects of dietary supplementation with porous zinc oxide on growth performance, intestinal microbiota, morphology, and permeability in weaned piglets. (4th July 2019) - Peng, Peng; Chen, Jiashun; Yao, Kang; Yin, Yulong; Long, Lina; Fang, Rejun
Abstract: The objective of this experiment was to evaluate the effects of dietary supplementation with porous zinc oxide (HiZox) on growth performance, intestinal microbiota, morphology, and permeability in weaned piglets. A total of 128 weaned piglets [(Landrace × Yorkshire) × Duroc] with an average body weight (BW) of (6.55 ± 0.25 kg; 21 d of age) were randomly assigned to four dietary treatments: (1) a corn‐soybean basal diet; (2) basal diet + 3, 000 mg/kg conventional ZnO; (3) basal diet + 200 mg/kg HiZox; (4) basal diet + 500 mg/kg HiZox. The experiments lasted for 28 days. Incremental HiZox in the diet increased ADG (linear p  = 0.015; quadratic p  = 0.043) and ADFI (linear p  = 0.027; quadratic p  = 0.038), and the diarrhea index decreased linearly and quadratically ( p  < 0.01) as HiZox supplemented increased. Furthermore, supplementation with HiZox increased the amounts of Lactobacillus spp. ( p  < 0.05) in the ileum and cecum in comparison with that of control treatment or 3, 000 mg/kg ZnO treatment, while decreased the populations of Escherichia coli, Clostridium coccoides, and Clostridium. leptum sub group ( p  < 0.05) in the ileum and cecum relative to those in control treatment. The addition of HiZox increased the villus height and villus‐to‐crypt ratio (VC) of duodenum, jejunum, and ileum ( p  < 0.05), while decreased the crypt depth of jejunum ( p  < 0.05) and tended to reduce the crypt depth of duodenum ( p  < 0.10) compared with the control treatment. Piglets fed with 500 mg/kg HiZox had lower serum D‐lactate and diamine oxidase (DAO) than those fed with basal control diet or 3, 000 mg/kg ZnO diet ( p  < 0.01). The results suggested that supplementation with HiZox modulated intestinal microbial composition and improved intestinal morphology, which may exert protective effects on the integrity of the mucosal barrier function of weaned piglets, was as efficacious as pharmaceutical doses of ZnO in enhancing growth performance, indicating that the HiZox may be a promising alternative to pharmaceutical doses of ZnO.